Brow set design background and practical learnings from Panel 0 block at Oyu Tolgoi underground mine - Ganbold, B.-E.; Ooi, J.; Baitag, B.; Baasanjav, B.; Stobbart, P. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Drawpoint stability and reliability are critical for caving mining productivity, and brow sets are one of the critical support elements dictating drawpoint production life. This paper outlines the design philosophy, installation approach and current performance of brow steel sets at the Oyu Tolgoi underground mine. The Hugo North orebody at Oyu Tolgoi contains several major geological structures within the Panel 0 caving footprint, and some drawpoints are located within fault zones. These faults and poor ground conditions adversely affect the rock brow stability and often lead to early brow erosion. To mitigate these risks, preconsolidation measures and brow set repair strategies have been incorporated into this study. Determining the demand for brow sets during the study stage is challenging due to operational uncertainties. The selection of brow steel sets depends on expected ground conditions and anticipated reserve tonnage or production life span. Benchmarking brow erosion from other block caving operations was also used to determine the appropriate rock brow distance to the brow set. The initial concept design comparisons for brow sets included the following options: